2007
DOI: 10.1007/s10551-006-9299-7
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Corporate Ethics in Marketing Genetic Tests

Abstract: biotechnology, genetic testing, disease susceptibility, pharmacogenomics, corporate ethics, business ethics, marketing, commercialization, intellectual property rights, truth in advertising,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…However, some tests like AmpliChip P450 aimed at predicting CYP2D6 and 2C19 gene polymorphisms are cleared by FDA and are available commercially. However if such tests are not linked to a particular disease or a particular drug, their penetration in clinical practice may be difficult (Williams-Jones et al 2007). Understandably, clinicians may be hesitant to apply pharmacogenetic testing as long as the regulation of various tests varies (Morley and Hall 2004), and there are no guidelines based on large sample sized studies to document their utility at the point of patient care (Ozdemir et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, some tests like AmpliChip P450 aimed at predicting CYP2D6 and 2C19 gene polymorphisms are cleared by FDA and are available commercially. However if such tests are not linked to a particular disease or a particular drug, their penetration in clinical practice may be difficult (Williams-Jones et al 2007). Understandably, clinicians may be hesitant to apply pharmacogenetic testing as long as the regulation of various tests varies (Morley and Hall 2004), and there are no guidelines based on large sample sized studies to document their utility at the point of patient care (Ozdemir et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that existing business practices are problematic, taking into account how the lack of a strong regulatory framework around the promotion of preventive medical genetic tests increases consumers' vulnerability since their knowledge of these highly sophisticated products/services is limited. In a similar vein, Williams-Jones and Ozderim (2008) argued that the growing consumer marketplace for genetic tests introduces a diversity of ethical challenges and questions such as the provision of misleading and inaccurate advertising for disease susceptibility. The authors elaborated on the infusion of pre-existing fears about a disease by reductionist marketing strategies which could increase consumers' anxiety towards the potential presence and development of a 'genetic' illness, and consequently, individuals' desire to buy and use genetic tests so as to reduce the risk.…”
Section: Genetics and Marketing Researchmentioning
confidence: 99%
“…The popularity and dynamic growth of genetic testing, which involves the introduction and commercial use of almost ten new tests annually, reinforces and substantiates the argument that genetic tests might substitute antibiotics in the 21 st century (Klitzman, 2012). Despite several sensitive and ethical issues --which emerge from the employment of predictive and diagnostic genetic tests, its commercial use via 'direct-to-consumer' practices significantly increases in various countries around the world (Berg & Fry-Edwards, 2008;Gollust, Hull & Wilfond, 2002;Liu & Pearson, 2008;Williams-Jones & Ozderim, 2008). Such increase regarding the popularity of DNA ancestral and health-related genetic testing has created a global marketplace whose main characteristics can be summarized to online services, imaginative promotion and product diversification.…”
Section: The Introduction Of Genetic 'Products'mentioning
confidence: 99%
“…Nevertheless, for health communication and health policy scholars, such uncontrolled exposure to information on sensitive products like drugs, genetic testing and innovative medical interventions are cause for concerns, raising social and ethical issues (Williams-Jones and Ozdemir, 2008). Several studies on direct-toconsumer online advertising and sale in such areas concluded that it can threaten information privacy, challenge equitable and safe access to healthcare, increase exposure to unreliable and biased information (Williams-Jones, 2006;Geransar and Einsiedel, 2008;Boden and Diamond, 2008;Berg and Fryer-Edwards, 2008), impact negatively the patient/physician relationship (Mitka, 2008;Racine et al, 2008), corrupt the physician/ industry relationship, and increase overall spending in medical care (Jost, 2010).…”
Section: The Web As a Space For Corporate Relationship Buildingmentioning
confidence: 99%